Influência da expansão rápida da maxila nas alterações volumétricas ocorridas na porção retropalatal e retroglossal - Haje, Ossam Abu El (2016)
Rapid maxillary expansion (RME) is an orthodontic procedure commonly used to correct transverse deficiencies by dividing the maxillary suture. Despite being routinely done for decades, its effects on the airways could only be assessed with precision by the advent of CT scans. The aim of this study was to investigate the volumetric changes of the upper airways on the retroglossal and retropalatal regions generated by rapid maxillary expansion (RME) and its stability after a period of 120 days. This was an analytical observational study of 28 computed tomography cone beam (CBCT) of 14 patients between 10 and 15 years. Each scan was performed before and after ERM 120 days and treatment. The delimitation of the airways and the determination of their volume was performed in two ways: as a (upper limit - Posterior nasal spine to the point basion and lower limit - the soft palate the uppermost portion of the epiglottis); and Measure B (upper limit - lower limit and palatal plane - anterior portion of the C3 vertebra). the paired t test with a 5% significance level was used. By comparing the measurements before and after ERM 120 days, both as A (10.5 ± 4.4 cm3 and 17.7 ± 7.0 cm3), as the measure B (9.4 ± 3.9 cm3 and 14.1 ± 5.5 cm3) demonstrated a statistically significant increase (p <0.0001) in the volume of the upper airways after RME, with no difference between the measures used (p = 0.49). It was concluded that both measures used in determining airway found increased volume of these after RME